2006 International Conference on Image Processing 2006
DOI: 10.1109/icip.2006.312886
|View full text |Cite
|
Sign up to set email alerts
|

Selective Encryption of Human Skin in JPEG Images

Abstract: In this study we propose a new approach for selective encryption in the Huffman coding of the Discrete Cosine Transform (DCT) coefficients using the Advanced Encryption Standard (AES). The objective is to partially encrypt the human face in an image or video sequence. This approach is based on the AES stream ciphering using Variable Length Coding (VLC) of the Huffman's vector. The proposed scheme allows the decryption of a specific region of the image and results in a significant reduction in encrypting and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 5 publications
0
16
0
1
Order By: Relevance
“…Real-time The experiments have shown that we can achieve the desired level of encryption in each frame, while maintaining the full AVS video coding standard compliance, under a minimal set of computational requirements. The proposed system can be extended to protect only ROI [17] in video surveillance and can be applied to medical image transmission [18].…”
Section: Resultsmentioning
confidence: 99%
“…Real-time The experiments have shown that we can achieve the desired level of encryption in each frame, while maintaining the full AVS video coding standard compliance, under a minimal set of computational requirements. The proposed system can be extended to protect only ROI [17] in video surveillance and can be applied to medical image transmission [18].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it is perfect for multimedia playback on handheld devices. The proposed system can be extended for ROI specific video protection [11] for video surveillance and can be applied to medical image transmission [10]. …”
Section: Resultsmentioning
confidence: 99%
“…The proposed system was suitable for video distribution to users who had subscribed to a different video quality regarding bandwidth, storage, and device rendering capabilities. The same system can be extended to ROI for bit-rate reduction in video surveillance [31], [51] without any modification. The error resilience [52] issues for the proposed system can be investigated in the transmission scenarios of scalable layers as a future work.…”
Section: Discussionmentioning
confidence: 99%